S02.1 Sex and relationships education in schools: a key component of sexual health promotion. (13th September 2015) - Aggleton, Peter
Abstract : Despite scientific evidence of effectiveness, there continues to exist controversy about sex and relationships education (SRE). Much of this relates to misunderstandings about the form that good quality SRE takes and what it aims to achieve. The evidence reveals that well designed and effectively implemented programs of comprehensive sexuality education have the potential to bring about beneficial outcomes for young people. But such programs often work best when they are implemented through partnership between education and health. Building on the framework offered by WHO in its guidance on Developing Sexual Health Programmes, this presentation highlights some of the ways in which this can be achieved: through the provision of in-school clinics and other health services; through effective signposting and fast-track routes to relevant services; and through health professionals' involvement in the life of the school. It signals the importance of understanding differences in culture and tradition between the education and health sectors, stressing how teachers, educational administrators and health professionals often understand 'intervention' and 'education' quite differently. Finally, it will stress the importance of respect for difference, and respect for the 'other' in work in schools.